“Efecto de las fases lunares en la producción del cultivo del maíz (zea mays L.) variedad marginal 28-tropical en el distrito de Juan Guerra- Provincia de San Martín” - Sánchez Santa Cruz, Henry Ali (2012)
This research paper entitled "Effect of the lunar phases in the production of maize (Zea mays L.) variety Marginal 28 - Tropical in the District of Juan Guerra, Province of St. Martín", was conducted in order to evaluate the agronomic performance and best performance of maize, variety Marginal 28 - Tropical, according to lunar phases, which was used fors tatistical design of completely randomized blocks withfour blocks, fourtreatments, which variables studied were: plantheight, earheight, 100 seedweight, grainyield (Tn/ha-1), assessment of disease (Spodoptera frigiperda, Usti/ago maydis, Helminthosporium maydis). There sults indicate that treatments Waning (CM) and Full Moon (L.LL), ledtheplantto be viable and strong responses in the studied variables of plan theight (cm), earh eight (cm), weight of 100 seeds (g), which ruled them to promote growth and development of the plant, and the high eryields of grain (Kg.ha-1), in maize, using Marginal range 28 - Tropical. Waning treatments (CM) and Full Moon (LLL) were those who obtained the highest grain yield (3548.36 and 3783.08 Kg.ha-1). The presence of pests and diseases did not cause economic damage in all treatments studied. Key words: Com, 28-Tropical Marginal variety, agronomic performance, moonphases, 100 seedweight, grain yield in Kg.ha-1 .